2012
DOI: 10.1111/j.1476-5829.2012.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone marrow aspirates from multiple sites for staging of canine lymphoma and mast cell tumours

Abstract: This prospective study evaluated the utility of bone marrow aspirates (BMAs) obtained from multiple sites for staging of canine lymphoma (LSA) and mast cell tumours (MCTs). Forty dogs (LSA, n = 24; MCTs, n = 16) were enrolled, but only 33 (82.5%) had diagnostic bone marrow (BM) aspirates obtained from two sites for inclusion in the study. Nineteen dogs with LSA were included, and 6 (31.6%) had BM involvement. Neoplastic lymphocytes were present in BM from both sites in all of these dogs. Fourteen dogs with MCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
13
0
3
Order By: Relevance
“…Although not being a primary goal of this investigation, the evaluation of bone marrow cytology findings also revealed no influence on treatment outcome. The observation that in the analysed dogs, whether or not lymphoma was accompanied by bone marrow involvement had no influence on the patients' remission and survival supports the above assumption that in lymphoma disease magnitude may not be of true importance . Hence, further, more sophisticated variables exerting stronger influence on the behaviour of this neoplasia in face of treatment must be identified.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although not being a primary goal of this investigation, the evaluation of bone marrow cytology findings also revealed no influence on treatment outcome. The observation that in the analysed dogs, whether or not lymphoma was accompanied by bone marrow involvement had no influence on the patients' remission and survival supports the above assumption that in lymphoma disease magnitude may not be of true importance . Hence, further, more sophisticated variables exerting stronger influence on the behaviour of this neoplasia in face of treatment must be identified.…”
Section: Discussionmentioning
confidence: 53%
“…Hence, further, more sophisticated variables exerting stronger influence on the behaviour of this neoplasia in face of treatment must be identified. For example, Kiupel et al evaluated the prognostic importance of Ki‐67, proliferating cell nuclear antigen (PCNA) and argyrophilic nuclear organiser region (AgNOR) and could demonstrate a benefit for AgNOR in predicting treatment outcome . Ponce et al demonstrated the prognostic significance of different lymphoma subtypes with shorter overall survival time and increased time of first remission in pleomorphic mixed and unclassified high‐grade plasmacytoid subtype of T‐cell lymphoma, a very short overall survival time in Burkitt type of B‐cell lymphoma, while small clear T‐cell lymphoma had a longer median time of first remission and longer overall survival time .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the observed decrease in CD3+ lymphocytes in fixed blood after 3 days was more relevant and could not be explained just by the variability of the methodology. Although the 21% decrease of CD3 expression between day 0 and 7 was not deemed clinically significant, and CD3+ T‐lymphocytes still made up the majority of all lymphocytes, such a variation may be of clinical relevance, particularly when evaluating small subpopulations of lymphoid cells in tissues (eg, flow cytometric evaluation of possible neoplastic infiltration in bone marrow) and in staging and monitoring of animals with lymphoproliferative disease …”
Section: Discussionmentioning
confidence: 99%
“…The local lymph node was sentinel to metastasis and, in the absence of lymph node metastasis, the utility of further staging was low (Warland et al 2014). However, in some tumours and sites the predicted lymphatic drainage is not clinically evident and some oncologists still advocate abdominal ultrasound and FNAs of liver and spleen in all dogs with MCTs, plus bone marrow evaluation in high-risk patients (Aubry et al 2014).…”
Section: Example 2: Canine Mctsmentioning
confidence: 99%
“…However, in some tumours and sites the predicted lymphatic drainage is not clinically evident and some oncologists still advocate abdominal ultrasound and FNAs of liver and spleen in all dogs with MCTs, plus bone marrow evaluation in high‐risk patients (Aubry et al . ).…”
Section: Introductionmentioning
confidence: 97%